2018
DOI: 10.1177/0363546517748924
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Graft Fixation Methods on Revision Rates After Primary Anterior Cruciate Ligament Reconstruction

Abstract: When comparing ACL graft fixation methods in the 4 categories using an HT graft, cortical suspensory fixation was found to have a significantly increased risk of revision, while intratunnel transfixation exhibited a lower risk of revision. Both Endobutton/Intrafix and Endobutton/Biosure PEEK implant combinations exhibited a significantly higher risk of revision. For PT grafts, Atlantech metal screw/metal screw and Softsilk/Softsilk exhibited a significantly lower risk of revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 33 publications
(42 reference statements)
1
54
1
1
Order By: Relevance
“…Combined data from all three registers showed that transfemoral hamstring tendon autograft fixations (Rigidfix and Transfix) reduced the risk of revision by 30% compared with Endobutton 25. In the DKRR, use of cortical suspensory fixation increased the 2-year risk of revision ACL reconstruction compared with all other categories for femoral fixation (adjustable cortical suspensory fixation, intratunnel transfixation and interference screw) (HR 1.24 [95% CI 1.07 to 1.44], p<0.05), while intratunnel transfixation lowered the risk of revision (HR 0.83 [95% CI 0.73 to 0.95], p<0.05) 24. The combinations Endobutton/Intrafix and Endobutton/Biosure PEEK for hamstring tendon autograft femoral/tibial fixation exhibited an increased risk of revision, while the lowest risk was found among combinations used for fixation of patella tendon autografts 24.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined data from all three registers showed that transfemoral hamstring tendon autograft fixations (Rigidfix and Transfix) reduced the risk of revision by 30% compared with Endobutton 25. In the DKRR, use of cortical suspensory fixation increased the 2-year risk of revision ACL reconstruction compared with all other categories for femoral fixation (adjustable cortical suspensory fixation, intratunnel transfixation and interference screw) (HR 1.24 [95% CI 1.07 to 1.44], p<0.05), while intratunnel transfixation lowered the risk of revision (HR 0.83 [95% CI 0.73 to 0.95], p<0.05) 24. The combinations Endobutton/Intrafix and Endobutton/Biosure PEEK for hamstring tendon autograft femoral/tibial fixation exhibited an increased risk of revision, while the lowest risk was found among combinations used for fixation of patella tendon autografts 24.…”
Section: Resultsmentioning
confidence: 99%
“…In the DKRR, use of cortical suspensory fixation increased the 2-year risk of revision ACL reconstruction compared with all other categories for femoral fixation (adjustable cortical suspensory fixation, intratunnel transfixation and interference screw) (HR 1.24 [95% CI 1.07 to 1.44], p<0.05), while intratunnel transfixation lowered the risk of revision (HR 0.83 [95% CI 0.73 to 0.95], p<0.05) 24. The combinations Endobutton/Intrafix and Endobutton/Biosure PEEK for hamstring tendon autograft femoral/tibial fixation exhibited an increased risk of revision, while the lowest risk was found among combinations used for fixation of patella tendon autografts 24. Similar results have been reported also from the NKLR,26 while two studies contradict these findings by stating that femoral fixation did not influence the risk of revision 11 17.…”
Section: Resultsmentioning
confidence: 99%
“…27 Graft-related factors (eg, type and method of fixation) have been reported as risk factors for subsequent (revision or contralateral) ACLR. 11,18,19 Based on previous studies in patients who underwent primary ACLR, the rate of primary ACL graft rupture ranges from 4.4% to 7.7%, whereas the rate of contralateral ACL rupture in those patients falls between 4.4% and 11.8%. 15,19,43 However, other variables have also been identified as independent risk factors for revision ACLR, including age, sex, race, body mass index (BMI), activity level, smoking status, and concomitant injury.…”
mentioning
confidence: 99%
“…The success of arthroscopic ACL reconstruction depends on several factors, including graft tension during fixation, 4 type and source of the graft, 5 tunnel position, 6 knee flexion angle at the time of fixation, 7 method of graft fixation, 8 and initial graft tension at the time of fixation. 9 Of these variables, the amount of tension applied during graft fixation has been hypothesized to be an important determinant of successful ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%